51.4k views
4 votes
How do i solve this using elimination to get an ordered pair?​

How do i solve this using elimination to get an ordered pair?​-example-1
User RodeoClown
by
4.9k points

1 Answer

5 votes

Answer:

The ordered pair would be (-2, 1)

Explanation:

To solve and get an ordered pair, we need to get a term to cancel. We can do this by multiplying the entire second equation by 2

4x + 3y = -5

-4x + 4y = 12

-------------------

7y = 7

y = 1

Now that we have the value of y, we can use it to find x.

-2x + 2y = 6

-2x + 2(1) = 6

-2x + 2 = 6

-2x = 4

x = -2

User Sameer
by
5.5k points